2018
DOI: 10.1021/acs.jpcc.8b03745
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Microtitration of Intermediates of Water Oxidation Reaction at Nanoparticles Assembled at Water/Oil Interfaces

Abstract: Photo-driven water oxidation reaction (WOR) at nanoparticles assembled at polarized liquid–liquid interfaces is a possible realization of the anodic reaction for water splitting at chemically polarized liquid–liquid interfaces. The rational development of a photocatalyst for the WOR requires their characterization under appropriate process conditions. A micropipette filled with an aqueous dispersion of nanostructured BiVO4 as a well-defined photoactive substrate is immersed into an immiscible organic solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…SECM was used to study the reaction of photogenerated holes and conduction band electrons at nanoparticle‐decorated liquid|liquid interfaces . The surface interrogation mode (SI‐SECM), which can be considered as a transient feedback experiment, was used to assess the amount and the decay kinetics of photogenerated surface‐bound intermediates of the water oxidation reaction at BiVO 4 ‐decorated liquid|liquid interfaces …”
Section: Introductionmentioning
confidence: 99%
“…SECM was used to study the reaction of photogenerated holes and conduction band electrons at nanoparticle‐decorated liquid|liquid interfaces . The surface interrogation mode (SI‐SECM), which can be considered as a transient feedback experiment, was used to assess the amount and the decay kinetics of photogenerated surface‐bound intermediates of the water oxidation reaction at BiVO 4 ‐decorated liquid|liquid interfaces …”
Section: Introductionmentioning
confidence: 99%
“…This study represents a step forward in the development of the batch water splitting process, as it dispenses with the use of sacrificial electron donors, generates a stable oxidized product that can be easily reduced and therefore recycled, and can operate under biphasic conditions for water splitting. Thus, [Cp 2 *Ru II ] coupled with an OER catalyst such as BiVO 4 , already studied at soft interfaces, is an attractive alternative for photoproducing H 2 fuel. Importantly, these investigations represent major progress in the general understanding of the photoproduction of H 2 by metallocenes through resolution of the mechanism involved.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21] The reversible redoxn ature of the metallocene [electron donor (D)] is the key,a si topens an ew perspective in solar fuel generation, because the oxidized electron donor (D + )c an be regenerated by ar educed electron acceptor (A À ). The latter can be sourced from as econd half-reaction, ideally light-driven oxygen evolutioni no rganic media [22][23][24][25][26] and, in theory, both photosystems will be "reset" by mixing the oil phases after photoirradiation (i.e.,D + + +A À !D+ +A). This concept has been termed "batch water splitting" ( Figure 1) and was discussed in more detail previously.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering work demonstrated the titration of surface oxides on gold and platinum electrodes, , after which SI-SECM was rapidly expanded to study surface sites and intermediates in oxygen electrocatalysis ,, and photoelectrocatalysis. Ahn and Bard performed time-dependent measurements in a neutral electrolyte and revealed different OER activities for different oxidation states in an anodically formed CoP i material. In another SI-SECM study, the coexistence of Ir IV and Ir V oxides during the OER was shown in an alkaline solution.…”
Section: Introductionmentioning
confidence: 99%